Fantasy and myth in the Anthropocene : imagining futures and dreaming hope in literature and media - Oziewicz, Marek; Attebery, Brian, 1951-; Dědinová, Tereza, 1982- (Bloomsbury Academic, 2022)
The first study to look at the intersection of the discourse of the Anthropocene within the two highly influential and perennially popular storytelling modes of fantasy and myth, this book articulates the idea that if humanity is to have a future, it needs stories that articulate visions of a biocentric, ecological civilization. As the two story systems that have been humanity's most advanced technologies for collective dreaming, fantastic fiction and myths are helping us adopt a biocentric lens, re-kin us with other forms of life, and assist us in the transition to an ecological civilization. Deliberately moving away from dystopian narratives toward anticipatory imaginations of sustainable futures, this volume blends chapters by top scholars in the fields of climate fiction, science fiction, fantasy, myth, and Young-Adult literature studies with personal reflections by award-winning authors and illustrators of speculative fiction for young audiences such as Jeff Vandermeer, Shaun Tan, Jane Yolen, Katherine Applegate and Joseph Bruchac. Covering the works of major fantasy authors such as J. R. R. Tolkien, Terry Prachett, J. K. Rowling, China Mieville, Barbara Henderson, Jeanette Winterson, John Crowly, Richard Powers, George R. R. Martin and Kim Stanley Robinson, and offering interrogations of cultural expressions set in or from the UK, USA, Nigeria, Ghana, Pacific Islands, New Zealand and Australia, this book frames fantasy and myth as spaces where visions of sustainable futures can be designed with most detail and nuance. Rather than merely criticizing the ecocidal status quo, the book asks how Fantastic stories can mobilize resistance around ideas necessary for the emergence of an ecological civilization.